Critical Assessment of Clean-Up Techniques Employed in Simultaneous Analysis of Persistent Organic Pollutants and Polycyclic Aromatic Hydrocarbons in Fatty Samples - Lucie Drábová; Darina Dvořáková; Kateřina Urbancová; Tomáš Gramblička; Jana Hajšlová; Jana Pulkrabová (Toxics, 2022)
Interference of residual lipids is a very common problem in ultratrace analysis of contaminants in fatty matrices. Therefore, quick and effective clean-up techniques applicable to multiple groups of analytes are much needed. Cartridge and dispersive solid-phase extraction (SPE and dSPE) are often used for this purpose. In this context, we evaluated the lipid clean-up efficiency and performance of four commonly used sorbents—silica, C18, Z-Sep, and EMR-lipid—for the determination of organic pollutants in fatty fish samples (10%) extracted using ethyl acetate or the QuEChERS method. Namely, 17 polychlorinated biphenyls (PCBs), 22 organochlorine pesticides (OCPs), 13 brominated flame retardants (BFRs), 19 per- and polyfluoroalkyl substances (PFAS), and 16 polycyclic aromatic hydrocarbons (PAHs) were determined in this study. The clean-up efficiency was evaluated by direct analysis in real time coupled with time-of-flight mass spectrometry (DART-HRMS). The triacylglycerols (TAGs) content in the purified extracts were significantly reduced. The EMR-lipid sorbent was the most efficient of the dSPE sorbents used for the determination of POPs and PAHs in this study. The recoveries of the POPs and PAHs obtained by the validated QuEChERS method followed by the dSPE EMR-lipid sorbent ranged between 59 and 120%, with repeatabilities ranging between 2 and 23% and LOQs ranging between 0.02 and 1.50 µg·kg−1.